2019
DOI: 10.3390/ijerph16244996
|View full text |Cite
|
Sign up to set email alerts
|

Study on Pre-Exposure Prophylaxis Regimens among Men Who Have Sex with Men: A Prospective Cohort Study

Abstract: Background: There are limited studies on the medication regimen of pre-exposure prophylaxis (PrEP) among men who have sex with men (MSM) in China. This study compared the effectiveness of and adherence to two prophylactic HIV medication regimens, which provided evidence and guidance for the application and promotion of the PrEP strategy in the MSM population in China. Methods: We conducted an open, non-randomized, multicenter, parallel, controlled clinical intervention study in western China. Subjects were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Our findings suggest that the MSM population in the event-driven group had higher adherence, which is consistent with Wu’s results [ 23 ]. In addition, MSM who had high-risk anal sex had lower adherence compared to MSM who did not.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings suggest that the MSM population in the event-driven group had higher adherence, which is consistent with Wu’s results [ 23 ]. In addition, MSM who had high-risk anal sex had lower adherence compared to MSM who did not.…”
Section: Discussionsupporting
confidence: 92%
“…If an illogical response occurs, participants will be reminded to answer the question again at the study site. Adherence ≥ 80% defined as "high-level" [ 20 , 22 , 23 ]. High-risk anal sex was defined as not using a condom during anal sex.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that age and risk profile were associated with one's choice of PrEP regimen [7], which subsequently affected the sexually transmitted infection (STI) incidence during PrEP use [8]. In open-label trials, breakthrough HIV infection was similarly uncommon for both daily and on-demand PrEP [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that age and risk profile were associated with one's choice of PrEP regimen [7], which subsequently affected the sexually transmitted infection (STI) incidence during PrEP use [8]. In open‐label trials, breakthrough HIV infection was similarly uncommon for both daily and on‐demand PrEP [7–10]. In Hong Kong, there have not been any government‐funded PrEP programmes and only patented TDF/FTC was available through prescriptions, the cost of which was well beyond the local MSM's affordability [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among MSM who are not infected by HIV, the efficacy and safety of long-term use of PrEP to prevent new HIV infection has been confirmed. [10][11][12] The US Centers for Disease Control and Prevention found that the use of PrEP can reduce the rate of HIV infection in high-risk individuals by more than 90%. 13 In 2015, the WHO officially included PrEP in its guidelines for preventing HIV infection in people who engage in high-risk sexual behaviors, indicating that PrEP is now a recognized means of preventing HIV infection.…”
Section: Introductionmentioning
confidence: 99%